Aplikasi Remote Sensing dan Sistem Informasi Geografis untuk Menunjang Database Lahan Pertanian Pangan Berkelanjutan di Subak Padanggalak - CAHYANINGRUM, FITRI; LANYA, INDAYATI; TRIGUNASIH, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.3, Juli 2021, 2021)
Application of Remote Sensing and Geographic Information System for Support Database of Sustainable Food Agricultural Land in Subak Padanggalak Subak Padanggalak is highly recommended as Sustainable Food Agricultural Land (SFAL). According to Government Regulation No. 25/2012, the SFAL implementation needs to be equipped with a geospatial-based database. The research aims: compile a database for support SFAL in Subak Padanggalak, create a land ownership map of Subak Padanggalak, create a geospatial-based SFAL information system, and land ownership of Subak Padanggalak. This research uses survey and mapping methods. Results from secondary data:  Typic tropaquepts , volcanic plains, micro slopes 0-3%, climate 1.500-2.000 mm/year, high soil fertility, potential land suitability for paddy is very suitable (S1), horticulture crops are moderately suitable (S2t) with temperature limiting factor. Results from primary data: (a) artificial resources: irrigation 16.236 m long, 1 m wide, good quality, semitechnical irrigation, jogging track 1.646 m long, 1,5 m wide, good quality, water source from Tukad Ayung, (b) agricultural resources: paddy, 7 ton/acre, paddy-paddy-paddy, Urea, and Phonska 175 kg/acre each, (c) human resources: mostly live in Kesiman Kertalangu, mostly primary school, farmers aged 35-80 years. The farmers status: 93 owner farmers (54,4%) and 78 sharecroppers (45,6%). The land ownership status: 330 freehold polygons (95.7%) and 15 non-freehold polygons (4.3%). Landowners amounted to 237 people, with the average of ownership is 0,43 acres/people.